A Prospective Observational Study of Ethnic and Racial Differences in Neuraxial Labor Analgesia Request and Pain Relief. Issue 2 (June 2015) - Wilson, S.H.; Elliott, M.P.; Wolf, B.J.; Hebbar, L.
Abstract : ( Anesth Analg . 2014;119(1):105–109)